Assessing the Effects of β-Triketone Herbicides on the Soil Bacterial and hppd Communities: A Lab-to-Field Experiment - Thiour-Mauprivez, Clémence; Devers-Lamrani, Marion; Bru, David; Béguet, Jérémie; Spor, Aymé; Mounier, Arnaud; Alletto, Lionel; Calvayrac, Christophe; Barthelmebs, Lise; Martin-Laurent, Fabrice (Frontiers in Microbiology, 2021)
Maize cultivators often use β-triketone herbicides to prevent the growth of weeds in their fields. These herbicides target the 4-HPPD enzyme of dicotyledons. This enzyme, encoded by the hppd gene, is widespread among all living organisms including soil bacteria, which are considered as “non-target organisms” by the legislation. Within the framework of the pesticide registration process, the ecotoxicological impact of herbicides on soil microorganisms is solely based on carbon and nitrogen mineralization tests. In this study, we used more extensive approaches to assess with a lab-to-field experiment the risk of β-triketone on the abundance and the diversity of both total and hppd soil bacterial communities. Soil microcosms were exposed, under lab conditions, to 1X or 10X the recommended dose of sulcotrione or its commercial product, Decano®. Whatever the treatment applied, sulcotrione was fully dissipated from soil after forty-two days post-treatment. The abundance and the diversity of both the total and the hppd bacterial communities were not affected by the herbicide treatments all along the experiment. Same measurements were led in real agronomical conditions, on three different fields located in the same area cropped with maize: one not exposed to any plant protection products, another one exposed to a series of plant protection products (PPPs) comprising mesotrione and a last one exposed to different PPPs including mesotrione and tembotrione, two β-triketones. In this latter, the abundance of the hppd community varied over time. The diversity of the total and the hppd communities evolved over time independently from the treatment received. Only slight but significant transient effects on the abundance of the hppd community in one of the tested soil were observed. Our results showed that tested β-triketones have no visible impact toward both total and hppd soil bacteria communities.